Anemia's Role in Premature Rupture of Membranes: Peran Anemia dalam Ketuban Pecah Dini - Isnaniyah; Rafhani Rosyidah (Academia Open, 2024)
Premature Rupture of Membranes (PROM) occurs before labor, typically at or beyond 37 weeks of gestation. This study investigates the relationship between anemia, Chronic Energy Deficiency (CED), and cesarean section history with PROM to aid early detection and prevention. Using a cross-sectional design, data from 94 third trimester pregnant women at the Wonoayu Health Center (January 2021 - June 2022) were analyzed. Results showed anemia was significantly associated with PROM (p=0.012), while CED and cesarean history were not. The study concludes that managing anemia in pregnant women is crucial to reduce PROM risk, highlighting the need for timely education and intervention. Highlight: Anemia significantly increases PROM risk. No link between CED, cesarean history, and PROM. Managing anemia crucial for PROM prevention. Keyword: Premature Rupture of Membranes, Anemia, Chronic Energy Deficiency, Cesarean Section, Pregnancy